Relation Between Past and Present Dietary Sugar Intake and Dental Caries in A High Caries Population - T. Malek Mohammadi; EJ. Kay; A. Hajizamani (Tehran University of Medical Sciences, 2008)
Objective: The main objective of this study was to investigate relationship between reported dietary habits and dental caries in five and six-year-old children referred for dental extractions. Materials and Methods: Two hundred children were examined using standard caries diagnostic criteria. The numbers of decayed, missing and filled deciduous teeth were recorded. A food frequency table was completed by the parents of each child and analyzed through weighting the cariogenic potential by the frequency of consumption, and summing the two scores. Results: The mean number of decayed, missing and filled teeth (dmft) was 7.1 (SD=3.29). There was no statistically significant correlation between the reported dietary intake and the caries rate in the study population P=0.07. Use of bottles with sugared drinks during infancy was associated with increased caries levels (P<0.01). Conclusion: Poor infant feeding practices promote caries in childhood. A method of diet assessment which would evaluate diet-related health education is required.